The Role of the Geometric Transformations in ihe Formation Process of the Function Concept - Szanyi, Gyöngyi; Vámosiné Varga, Adrienn (International Journal of Engineering and Management Sciences, 2020)
The concept of the function and the different geometrical transformations play important role in the technical sciences. Since geometric transformations are functions, so-called geometric functions, therefore, in this study, we present a possible way of that, how can we apply the animations of the geometrical transformations which are made with GeoGebra in the formation process of the function concept in the primary and secondary school level.